The Strength of Corporate Culture and the Reliability of Firm Performance - Sørensen, Jesper B. (Administrative Science Quarterly, 2002)
Prevailing research claims that strong corporate cultures improve firm performance by facilitating internal behavioral consistency. This paper addresses an unexamined implication of this argument by analyzing the effect of strong corporate cultures on the variability of firm performance. This relationship depends on how strong cultures affect organizational learning in response to internal and external change. I hypothesize that strong-culture firms excel at incremental change but encounter difficulties in more volatile environments. Results of analyses of a sample of firms from a broad variety of industries show that in relatively stable environments, strong-culture firms have more reliable (less variable) performance. In volatile environments, however, the reliability benefits of strong cultures disappear.